Evaluation of fluνalinate, methomyl and kinoprene on the greenhouse whitefly Trialeurodes vaporariorum West. (Homoptera: Aleyrodidae) - Roditakis Ν.Ε. (ENTOMOLOGIA HELLENICA, 1984)
The effectiveness of three insecticides, fluvalinate, kinoprene and methomyl (synthetic pyrethrin, juvenile hormone analog and organophosphate, respectively), against the greenhouse whitefly, Trialeurodes vaporariorum West. (Homoptera: Aleyrodidae), was evaluated in commercial greenhouses. The impact of chemicals was studied on isolated whitefly stages in a rearing room (24 ± I”C, 65 ± 5% R.H. and L:D 16:8h). Fluvalinate was the most effective toxicant through its broad activity on whitefly life stages. Kinoprene controlled 2nd and 3rd larval instars but a moderate effectiveness was noticed on eggs, first instar larvae and pupae. Methomyl was effective against first instar larvae and adults but it had no substantial effect on the other stages. Of the three materials tested only fluvalinate approached the total control requirements for a successful whitefly suppression.